The Mahabharata of Vyasa: Book XII The Complete Shanti Parva. Part 2: Moksha-Dharma. Translated from Sanskrit by Pradip Bhattacharya - Chaitanya, Satya (Religions of South Asia, 2018)
The Mahabharata of Vyasa: Book XII The Complete Shanti Parva. Part 2: Moksha-Dharma. Translated from Sanskrit by Pradip Bhattacharya. Kolkata: Writers Workshop, 2015. 1112 pp., Rs. 2000. ISBN 978-9-350-45122-9.